Diagnostic of ID Systems in Tunisia - World Bank (World Bank, Washington, DC, 2020)
This report presents the current state of identification (ID) systems in Tunisia and their use across sectors. Based on an initial study completed in 2018 by the World Bank’s identification for development (ID4D) initiative, it provides a summary of the strengths and weakness of the country’s primary ID systems and recommended next steps for developing an inclusive and trusted identity ecosystem that will improve governance and facilitate access to basic rights and services. This report is organized as follows: part one gives introduction. Part two provides an update on the status of identity projects and their progress since the benchmarking study commissioned by the Government of Tunisia (GoT) in 2015 that led to the development of the unique citizen identifier (IUC). It gives an overview of existing databases and credentials, as well as ongoing projects and issues with implementation. Part three provides a summary of the main achievements, as well as ongoing challenges and uncertainties regarding identification in Tunisia across these various systems and projects, and then provides recommendations for addressing these issues in the future.